“¿Cómo te sientes? – With my butt!”: code-choice-related humor in bilingual speakers living with dementia of the Alzheimer’s type - Schneider, Carolin; Qalaj, Besa (Journal of Language and Aging Research, 2023)
This study investigates data from three narrative interviews held with people living with early- and mid-stage dementia of the Alzheimer’s type (DAT) and their primary care partners speaking English and Spanish in informal settings; the analysis focuses on the humorous moves which are employed by the participants living with dementia in both languages. Drawing on the General Theory of Verbal Humor and the Cooperative Principle, this study sheds light on the conversational humor on a semantic (i.e. language-dependent) as well as pragmatic level (i.e. contextually situated) initiated by the people living with dementia in this dataset while investigating the interpersonal goals behind such moves. By analyzing the (intentional) humorous practices and their respective code choices, our aim is to gain a better understanding of the pragmatic abilities of speakers which are retained while experiencing communication challenges in the face of DAT. This study thus contributes with increased knowledge about people living with dementia as active conversational partners.